2006
DOI: 10.1128/jcm.44.4.1435-1439.2006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PCR Assays for Diagnosis of Cutaneous Leishmaniasis

Abstract: Three PCR assays for diagnosing leishmaniasis were compared and validated against parasite cultures and microscopic evaluation of stained tissue smears using 92 specimens from suspected cases of cutaneous leishmaniasis (CL) in Israel and the West Bank. Samples from imported and locally acquired disease were examined. The kinetoplast DNA (kDNA) PCR showed the highest sensitivity (98.7%) of any assay, correctly diagnosing 77/78 of the confirmed positive samples, followed by the rRNA gene internal transcribed spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
253
1
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(285 citation statements)
references
References 37 publications
21
253
1
6
Order By: Relevance
“…This could be due to the different PCR protocols (nested / conventional / real-time PCR; gene target) of respective studies, or because swabs do not contain a uniform cell number, depending on the technique of sampling. The most sensitive PCR assay is the method using kinetoplast DNA (kDNA), detecting the copy number of the target regions between 50-and 250-fold higher than splice leader mini-exon (SLME) and the SSU rRNA (ITS1) (Bensoussan et al 2006). In the present study, Leishmania DNA was found in blood samples, skin scrapings, joint punctures and in bone marrow.…”
Section: Leishmaniamentioning
confidence: 65%
See 1 more Smart Citation
“…This could be due to the different PCR protocols (nested / conventional / real-time PCR; gene target) of respective studies, or because swabs do not contain a uniform cell number, depending on the technique of sampling. The most sensitive PCR assay is the method using kinetoplast DNA (kDNA), detecting the copy number of the target regions between 50-and 250-fold higher than splice leader mini-exon (SLME) and the SSU rRNA (ITS1) (Bensoussan et al 2006). In the present study, Leishmania DNA was found in blood samples, skin scrapings, joint punctures and in bone marrow.…”
Section: Leishmaniamentioning
confidence: 65%
“…For this purpose, results of blood or serum samples sent by local veterinarians to a veterinary diagnostic laboratory were retrospectively analysed. Samples were examined for Leishmania spp., Babesia spp., Ehrlichia canis, Dirofilaria immitis and Anaplasma phagocytophilum during the years 2004-2006. Erythrocyte stages of large Babesia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Our result for PCR sensitivity when conserved region kDNA was used, showed a higher value 69.6% (95% CI 59.2-72.6%) than when ITS rDNA was used as molecular target. This difference could be due to differences in the number of copies present in Leishmania: around 10,000 copies for kDNA and near 200 copies for ITS rDNA (Rodgers et al 1990, Pirmez et al 1999, Marfurt et al 2003, Bensoussan et al 2006. Also, differences in the detection limits for each molecular target have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…As L. (L.) chagasi are intracellular parasites that infect cells of the mononuclear phagocytic system, like monocytes and macrophages, the use of the leukocyte layer instead of whole blood may increase sensitivity, reducing the interference of potential reaction inhibitors. PCR has gradually become the technique indicated to diagnose leishmaniasis, as conventional parasitology methods are not sufficiently sensitive 23,24 .…”
Section: Anthropogenic Parameters Of Ecological Disturbancementioning
confidence: 99%